The Application Uti Possidetis Principle in Africa - F. Mirzayev (Московский журнал международного права, 2016)
Uti possidetis originating from Roman jus civile which later transformed into a principle of interstate relations dealing with a transformation of former administrative borders into international boundaries of the newly independent states in Latin America was also effectively applied upon decolonisation in Africa in XX century. This article considers the relevant state practice of the African states and the OAU’s position on application of uti possidetis principle. The article also analyses the Burkina Faso vs Mali case which is one of the substantial cases on application of uti possidetis pinciple.